Adult Responsibility in Insecure Times - Crawford, Kate (Soundings, 2009)
Has adulthood as we once knew it been lost? Is the state of 'being adult' so eroded that immaturity, selfishness and infantilism have all but replaced it? You could be forgiven for diinking so, given the frequency with which media commentators, sociologists and cultural critics have discussed the refusal of today's youth to grow up. We read about it in newspapers, hear concerned debates on radio, and see it played out on TV and in cinemas - be it Friends, Fight Club, or Failure to Launch. The last decade saw the rapid popularisation of new terms such as 'kidult', 'adultescent' and 'rejuvenile' to designate those who seemed to live in an extended adolescence, enjoying life's youthful pleasures while remaining leery of orthodox commitments. Kidults lack 'direction, commitment and any sense of permanence', the newspapers inform us, as 'Big Brother, celebrity gossip and an iPod are more important'.1 But in spite of these widespread rumours of its demise, there has been little substantial discussion of what actually constitutes adulthood.